Integrasi Potensi Tambak Garam dalam Pembelajaran Kelas IV Sekolah Dasar Pesisir Madura - Ade Cyntia Pritasari; Conny Dian Sumadi; Hangrainy Prastiwi (Musamus Journal of Primary Education, 2022)
Madura Island has the greatest potential for the development of salt ponds in Indonesia. The great potential of salt ponds can be integrated into learning. There are many benefits and advantages to learning that integrate the local potential. The integration of the potential of salt ponds can be an effort to strengthen regional identity and character. This study aims to analyze the potential of Madura salt ponds in thematic learning in the fourth grade of elementary school. The research was carried out using a qualitative approach with the document analysis method. The Syllabus, elementary school student books, and relevant articles were analyzed as documents. Based on the results of the analysis, it was found that the potential of salt ponds can be integrated into fourth grade elementary school learning, namely on theme 7 subtheme 1. In this sub-theme, the potential of salt ponds can be integrated into the content of science, Indonesian, social studies, PPKN, and SBDP.